PIE PRODUCT INNOVATION THROUGH MUNG BEAN FLOUR SUBSTITUTION TO INCREASE FAMILY ECONOMIC PASSION - Mariah, Siti; Febriyany, Devy; Sari, Anggri Sekar (Prosiding Pendidikan Teknik Boga Busana, 2021)
The research objective was to determine the differences in the substitution of green bean flour with a percentage of 20% and 40%, the level of public preference, protein, and carbohydrate content in pies. The research used a pure experiment. The level of preference is done by providing products, questionnaires, and documentation. The data analysis technique used ANOVA analysis. The results showed: there were differences in color, texture, taste, and aroma in 20% and 40% green bean flour. Most of the panelists liked the color, taste, aroma, and texture of the 20% mung bean flour substitute pie. The substitution of 20% green bean flour has a high nutritional content of protein and carbohydrates. Thus, the substitution of mung bean flour into pie products is expected to increase family spirit and economic resilience. Keywords: Pie, substitution of green bean flour, family economic